Microscopic Description of Multinucleon Transfer in 40Ar + 64Ni collisions at 15 MeV/nucleon - Palli, Konstantina; Souliotis, George; Dimitropoulos, Ioannis; Depastas, Theodoros; Fasoula, Olga; Koulouris, Stergios; Veselsky, Martin; Bonasera, Aldo (HNPS Advances in Nuclear Physics, 2022)
This contribution deals with the study of the production mechanism of neutron-rich nuclei from heavy-ion peripheral reactions in the Fermi energy region. Experimental data from the reaction of 40Ar at 15 MeV/nucleon with 64Ni,58Ni targets, are considered. These data were collected with the MARS spectrometer at the Cyclotron Institute of Texas A&M University. Mass and momentum distributions, which provide valuable information on the reaction mechanisms, are presented and compared with calculations with two theoretical models: the Deep Inelastic Transfer (DIT) model and the Constrained Molecular Dynamics (CoMD) model. For the CoMD model, the parameters of the effective interaction in the original code were systematically varied in order to satisfactory describe the experimental data, with main focus on the effect of the Pauli constraint and the compressibility on the calculations.